English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-11 11:13:10 · 3 answers · asked by grim reaper 2 in Science & Mathematics Mathematics

3 answers

Factor out x:

x(x + 12) = 0

So either x = 0 or

x + 12 = 0

x = -12

2007-01-11 11:35:11 · answer #1 · answered by Jim Burnell 6 · 0 0

First factor out common terms... in this case, both terms have an x.

x(x+12) = 0

Then set each term =0 and solve for x.

x = 0

x + 12 = 0
x = -12

2007-01-11 19:35:24 · answer #2 · answered by Mathematica 7 · 0 0

x= -12

x^2 +12x=0

x^2/x = -12x/x

(x's cancel out)

therefore x= -12

2007-01-11 21:17:34 · answer #3 · answered by Anonymous · 0 1

fedest.com, questions and answers